Nanotubos magnéticos sintetizados por eletrodeposição em alumina anódica porosa - Chrischon, Dieivase da Silva (2016)
Magnetic materials when reduced to the nanoscale promote the emergence of new properties and the specific functionalization of these magnetic nanostructures are key tools in the development of improved devices for information technology (memory and data processing) and detection. In this thesis were electro-deposited magnetic nanotubes in anodic aluminum membranes. The properties of magnetic nanotube networks of Ni, Co, FeCo and FeNi with different geometric parameters were investigated. The porous aluminum oxide membranes were prepared using the hard anodizing process, in a self-ordering regime with pore distances Dint=300nm. This process offers substantial advantages over conventional anodizing processes in terms of processing time, allowing for faster oxide growth, with better arrangement and high aspect ratio of nanopores. The nanotubes were electrodeposited through the potentiostat mode, using porous membranes as the basis for their structure. Samples with external diameter of 140nm, 180nm and 220nm were obtained. In addition, the nanotubes have an additional degree of freedom given by the thickness of the tube walls. In this way, nanotubes with constant external diameter and different wall thicknesses of the tube were also synthesized. The structure and morphologies of the synthesized samples were characterized by scanning electron microscopy, x-ray dispersion spectroscopy and x-ray diffraction. The magnetic characterization was performed through the vibrating sample magnetometer. Through the nanotubes with different diameters it was possible to observe that the global anisotropy of the matrix is the result of the competition between the magnetostatic interactions, magnetocrystalline anisotropy and form anisotropy. With the increase of the diameter of NTs and the decrease of the distance between them it was observed that the magnetostatic interactions prevail. Nanotubes with different wall thicknesses were produced, maintaining constant the external diameter and the distance between the structures. Through the characterization of these structures it was observed that for nearby nanotubes, with distances smaller than their diameter, it is the wall thickness that determines the magnetic interaction between the nanotubes of the network. The magnetization inversion processes for NTs with different wall thicknesses were investigated through the analysis of the coercive field as a function of the applied field. It can be seen that the same structure can present two types of magnetization inversion, the transverse mode or vortex, and that this inversion can be determined by adjusting the NT wall thickness. The comparative study between the nanotubes with different compositions and geometric parameters showed that the magnetic properties are strongly correlated with the geometric parameters.